Pelatihan dan Pendampingan Persiapan Ulangan Asesmen ANBK Berbasis Komputer di SD Negeri 75 Locok - Irfan Fadrian Ramadan; Cheriani; Andi Hajar (Komunitas Dosen Indonesia, 2024)
The reason for this service is the introduction of the Computer-Based National Assessment (ANBK) in elementary schools. The implementation of ANBK at the primary school level requires a lot of preparation, including preparing students who are not yet computer-savvy to take computer-based assessments. The purpose of this service is to introduce students to computers in general and deepen their understanding of ANBK materials. This service is delivered with a Participatory Action Research (PAR) approach. The approach is in the form of computer introduction activities, deepening material and question analysis, and ANBK simulations. This service is carried out in collaboration with the service team and school managers or school administrators. The training participants amounted to 16 Grade V students of SD Negeri 75 Locok. This service provides understanding and knowledge that students can implement into the ANBK system on their computers. This can be seen from students who better understand the basics of computers, are fluent in entering personal information, understand ANBK materials, and are able to complete ANBK simulations successfully